Prevalence and significance of CYP2C19*2 and CYP2C19*17 alleles in a New Zealand acute coronary syndrome population. Issue 5 (May 2015) - Larsen, P. D.; Johnston, L. R.; Holley, A.; La Flamme, A. C.; Smyth, L.; Chua, E. W.; Kennedy, M. A.; Harding, S. A.
Abstract Background High on‐treatment platelet reactivity has been associated with poor outcomes following acute coronary syndromes (ACS). Both the loss of function CYP2C19*2 allele and the gain of function CYP2C19*17 allele along with a range of clinical characteristics have been associated with variation in the response to clopidogrel. Aim The study aims to examine the frequency of CYP2C19 variants and understand the factors associated with on‐treatment platelet reactivity in a New Zealand ACS population. Methods We prospectively enrolled 312 ACS patients. We collected clinical characteristics and measured on‐treatment platelet reactivity using two validated point‐of‐care assays, VerifyNow and Multiplate. DNA was extracted and CYP2C19*2 and *17 alleles were identified using real‐time polymerase chain reaction. Results CYP 2 C 19*2 or CYP2C19*17 alleles were observed in 101 (32%) and 106 (34%) of patients, respectively, with significant differences in distribution by ethnicity. In Maori and Pacific Island patients, 47% (confidence interval (CI) 31–63%) had CYP2C19*2 and 11% (CI 4–19%) CYP2C19*17 compared with 26% (CI 19–32%) and 41% (CI 32–49%) in white people. Carriage of CYP2C19*2 alleles was associated with higher levels of platelet reactivity measured by either assay, but we observed no relationship between platelet reactivity and CYP2C19*17. In multivariate analysis diabetes, clopidogrel dose and CYP2C19*2 status were all significant independent predictors of platelet reactivity. Conclusions Both CYP2C19*2 and *17 were common in a New Zealand ACS population, with CYP2C19*2 observed in almost half the Maori and Pacific Island patients. CYP2C19*2, diabetes and clopidogrel dose were independent contributors to on‐treatment platelet reactivity.